PENINGKATAN KETERAMPILAN MENULIS PUISI MELALUI PENGGUNAAN MEDIA AUDIOVISUAL PADA SISWA KELAS V SDN KELENG 01 - TUROFINGAH, LINA (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Lina Turofingah. Increase the Ability to Write a Poem  with use  Audiovisual  Media At V Grade Students Keleng 01 Elemantary School. The purpose of this research is to description use audiovisual media to increase the ability to write a poem, To increase student ability to write a poem and  know constraint and solution to increase the ability to write a poem using audiovisual media at V grade Keleng 01 Elementary School Kesugihan Cilacap Academic Year 2012/2013. This research uses class actions research methods are carried in the three cycles. Each cycle consists of planing, action, observation, and reflection. This research subject are students of V grade, there are 24 students. This data from student, teacher, observer, and studying procces. Data collecting methods are collected through observation, test, analysis student work, and questionnaire. The validity of data using the triangulation technic and resource. The analysis of data using analysis descriptive kuantitative technic. The research procedure using Spiral Kemmis model and Taggart Procedure include planning, action, observation and reflection. The result of research indicate through using audiovisual media can increase procces and student studying result with write a poem ability Keywords: Audiovisual media, The ability to write a poem Abstrak: Peningkatan Keterampilan Menulis Puisi Melalui Penggunaan Media Audiovisual pada Siswa Kelas V SDN Keleng 01. Penelitian ini bertujuan mendeskripsikan langkah-langkah penggunaan  media audiovisual, meningkatkan keterampilan menulis puisi siswa serta  mengetahui kendala dan solusi penggunaan media audiovisual. Penelitian ini menggunakan metode  penelitian tindakan kelas yang dilaksanakan dalam tiga siklus. Setiap  siklus terdiri atas perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas V dengan jumlah 24 siswa. Data bersumber dari siswa, guru, observer, dan proses pembelajaran. Teknik pengumpulan data meliputi: observasi, angket dan tes dan analisis kerja murid.  Validitas data menggunakan triangulasi teknik dan sumber. Analisis data menggunakan teknik analisis deskriptif kuantitatif. Prosedur penelitian menggunakan model Spiral Kemmis dan Taggart  yang terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Hasil penelitian  menunjukkan bahwa langkah-langkah penggunaan media audiovisual secara tepat dapat meningkatkan keterampilan menulis puisi siswa. Kata Kunci: Media Audiovisual, Keterampilan Menulis Puisi